Tod im Kino Indexikalisches Sterben in ikonisch-symbolischen Ordnungen des kinematographischen Diskurses - Seelinger, Christoph (Büchner-Verlag, 2022)
In his doctoral dissertation, Christoph Seelinger provides an overview of strategies for legitimizing and functionalizing documentary death scenes in narrative cinema. Seelinger's chronological arc begins with the earliest animal deaths on camera, such as the filmed execution of the female elephant Topsy in »Electrocuting an Elephant - Thomas A. Edison« (1903), and it continues to the glossy snuff videos of the Islamic State's media department in the 2010s. Between these two poles, the author - with the same academic scrutiny - looks at established arthouse films, but all also at countless representations of station cinema that have been dismissed as trash and exploitation and have so far eluded academic research. The result is a foray through the more ostracized regions of cinema history and, in the process, nothing less than the first detailed history of the intrusion of real depictions of death into the fiction of the feature film.